Meningkatkan Kinerja Karyawan dengan Komunikasi Internal dan Komitmen Organisasional - Wiguna, I Made Rai Artha; Kawiana, I Gede Putu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2022)
ABSTRACT Given the importance of performance, it is necessary to pay attention to the factors that affect employee performance, namely internal communication and organizational commitment. This study aims to determine the effect of internal communication partially on employee performance and organizational commitment partially on employee performance. This research was conducted at PT. Astrido Jaya Mobilindo in Denpasar. This research was conducted at PT. Astrido Jaya Mobilindo in Denpasar. The number of samples taken was 54 employees, with a saturated sampling method. Data collection was carried out through observation, interviews, documentation, literature and questionnaires. Based on the results of the analysis, it was found that there was a positive and significant influence between internal communication and organizational commitment partially on employee performance, and there is a positive and significant influence between internal communication and organizational commitment simultaneously on employee performance.